EFEKTIVITAS SISTEM LINGKUNGAN BAGI PENGEMBANGAN UMAT BERIMAN SESUAI KDPL KEUSKUPAN AGUNG SEMARANG - Andreas Budiyo (Jurnal Teologi (Journal of Theology), 2014)
This thesis examines the implementation of pastoral environments in Parish St. Peter and Paul, Babadan, Yogyakarta. And aims to look at the effectiveness of pastoral guidance for basic Christians community (lingkungan) based on KDPL (Kebijakan Dasar tentang Pastoral Lingkungan) for the development of the faithful in the lingkungan. Basis of existing policies that would encourage the development of pastoral environment would boost the faith of the faithful. This thesis uses quantitative and qualitative methods. The Qualitative methods using means of questions aimed at people in the lingkungan of St. Peter and Paul Babadan Parish. Key informants are faithful in the lingkungan. While quantitative methods by asking for some leader of lingkungan and parish priest. Basic theory of the research policies is KDPL in the Archdiocese of Semarang. The data then analyzed and formulated as a conclusion.